The effect of the war on Irish agriculture - Stanuell, Charles A. (Statistical and Social Inquiry Society of Ireland, 1915)
The subject of my address is not statistical. It is an attempt to show Irish farmers that as a result of the universal war prevailing in Europe we shall have in all probability a bad shortage of all kinds of provisions, both corn and meat, next year and probably the year after, and my object is to urge them to increase their tillage, including in this expression, turnips, mangold and other forms of food for cattle and stock, so as to provide meat ready for market, instead of exporting them alive to be "finished."
Read Friday, November 13, 1914.
Keywords: Food supply, World War One; Agriculture, World War One; 314.15